Enhancing Students' Online Engagement: A Study on Online Distance Learning Institutions' Students - Zahir Osman; Ratna Khuzaimah Mohamad; Liana Mohamad, (Global Academy of Training & Research (GATR), 2021)
Objective - This study evaluates the direct relationships among online learning attitude, online peer collaboration, psychological motivation, digital readiness, and online engagement among students in Malaysia's online distance learning (ODL) higher education institutions.